PENGARUH PENGGUNAAN CAMPURAN PUPUK ORGANIK FESES TERNAK SAPIN PADA USAHA TANI TOMAT (Lycopersicum Esculentum Mill. L.) TERHADAP EKONOMI PETANI: (Studi Kasus Di Desa Urung Purba Kecamatan Purba Kabupaten Simalungun) - Nainggolan, Mai Fernando; Saragi, Cyprianus P.H (Jurnal Manajemen dan Bisnis, 2022)
The first objective of this study is to analyze the costs, income and production of tomato farming using mixed organic fertilizers, for the second purpose, namely to analyze the factors that affect tomato farming using mixed organic fertilizers in Urung Purba Village, Purba District, Simalungun Regency). This research was conducted using the census method on 45 tomato farmers using organic mixed cow feces and single non-organic fertilizer. Data collection is done by interview, observation and documentation. Sources of data taken include primary data in the form of land area data, number of workers, labor wages, number of seeds, seed prices, amount of fertilizer used, fertilizer prices, tomato production/planting season period, selling prices of tomatoes, production costs, income as well as regarding the general condition of tomato farmers, and secondary data obtained from agencies related to this research such as the Office of Agriculture/Livestock in Urung Purba Village, Purba District, Simalungun Regency). Data analysis used the two-average difference test with two unpaired sample t-test techniques and cobb doubleglass production function analysis. The results of the analysis show that the cost of tomato farming using mixed organic fertilizers is Rp. 32,936,915 lower than the cost of tomato farming using a single non-organic fertilizer, which is Rp. 38,659,431 (real at 0.023), the income of tomato farming using fertilizers Mixed organic fertilizer was Rp.43,653,085, which was higher than tomato farming using a single non-organic fertilizer, which was Rp.34,938.069 (significantly at 0.002). The yield of tomato using mixed organic fertilizer was 30,636 kg higher than that of tomato farming using a single non-organic fertilizer, which was 29,439 kg (significantly at 0.030). The results of the analysis of the production function of cobb doubles mixed fertilizer show that the variable amount of organic fertilizer, the amount of non-organic fertilizer, the number of workers, the number of seeds and the amount of medicine have a significant effect on production with a probability of 0.005, as well as the analysis of the production function of a single non-organic fertilizer, showing the amount of fertilizer. non-organic, the number of workers, the number of seeds and the amount of medicine have a significant effect on production with a probability of 0.007.